The Impact Of The Operation Of Jati Asih Toll Gate On Land Use Changes In Jati Asih Sub-District - Tsamara Qolbi Haridza; Anita Sitawati Wartaman; Wisely Yahya (Politeknik Negeri Batam, 2022)
The construction of the JORR E1 (Cikunir-Jatiasih) toll road is expected to improve accessibility in Bekasi City, especially in Jati Asih District. The operation of the JORR E1 (Cikunir-Jatiasih) toll road in 2007 caused a change in land use in Jati Asih District, Bekasi City. On the other hand, the land use changes that occur are not in accordance with the Bekasi City Regional Regulation No. 5 of 2016 concerning Detailed Spatial Planning (RDTR). The area around the Jati Asih Toll Gate is designated as a mixed zone, but the existing condition of land use is for trade and service activities. This study aims to identify land use before the operation of the Jati Asih Toll Gate in 2006 and identify changes in land use after the operation of the Jati Asih Toll Gate in 2017. Descriptive statistical methods and spatial analysis were applied in this study by looking at land use changes at a radius of 1 km from the gate. JORR E1 (Cikunir-Jatiasih) toll road. This study shows that there is a change in land use around the Jati Asih sub-district, which is seen by the decrease in the area and distribution of the use of plantation land, moor, and vacant land from 2006-2017. Within a radius of 1 km from the Jati Asih Toll Gate in 2006-2017 there was a decrease in area and distribution on plantations, vacant land, and dry fields. This is inversely proportional to settlements and buildings, which experienced an increase in area and distribution from 2006-2017. Settlements and buildings also experienced an increase in area and distribution within a radius of 1 km from the Jati Asih Toll Gate in 2006-2017. Keywords: Land Use Changes, Toll road, Jati Asih District, Radius.